Leadership in the Era of Artificial Intelligence: Challenges, Opportunities, and Strategic Transformation - Fantoni, Muhammad Jefry; Sasmita, Jumiati (Journal Corner of Education, Linguistics, and Literature, 2025)
Leaders in the era of artificial intelligence face new dynamics that challenge traditional leadership models, including rapid technological disruption, organizational resistance, and increasing trust gaps between employees and executives. This study aims to explore the challenges, opportunities, and strategic transformations required for leadership in the context of artificial intelligence adoption. The research reviewed scientific articles published between 2019 and 2025 obtained through purposive sampling from databases such as Scopus, ScienceDirect, and ResearchGate, with inclusion criteria focusing on digital leadership, artificial intelligence, organizational change, and ethical implications. The systematic literature review method was used, supported by content analysis to identify and categorize themes. The findings indicate three major themes: first, leaders face challenges such as algorithmic bias, lack of digital literacy, and mental health pressures that may hinder organizational adaptation; second, artificial intelligence provides opportunities by enhancing decision-making accuracy, predictive analytics, and enabling inclusive human-machine collaboration; third, strategic transformation requires leaders to develop AI literacy, internalize ethical leadership, and establish long-term digital visions that balance efficiency with human sustainability. The study concludes that leadership effectiveness in the era of artificial intelligence depends not only on technological mastery but also on ethical responsibility, organizational adaptability, and strategic foresight. The implications highlight the urgent need for leadership training programs that integrate digital skills, ethical frameworks, and sustainability values to ensure organizational resilience in the future.